Floodplain zoning simulation by using HEC-RAS and CCHE2D models in the Sungai Maka river - ShahiriParsa A.; Noori M.; Heydari M.; Rashidi M. (Libertas Academica Ltd., 2023)
River flooding causes several human and financial casualties. It is necessary to perform research studies and implement subsequent actions consistent with the nature of the river. In order to reduce flood damage, floodplain zoning maps and river cross-sectional boundaries are important to nonstructural measures in planning and optimizing utilization of the areas around the river. Due to the complex behavior of the rivers during floods, computer modeling is the most efficient tool with the least possible cost to study and simulate the behavior of the rivers. In this study, one-dimensional model Hydrologic Engineering CentersRiver Analysis System and two-dimensional model CCHE2D were used to simulate the flood zoning in the Sungai Maka district in Kelantan state, Malaysia. The results of these two models in most sections approximately match. Most differences in the results were in the shape of the river. The authors.